Leadership Skills, Behaviors & Traits - Paul, Anil (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2017)
The author presents required leadership characteristics - 38 skills, 12 behaviors, and 9 traits - for project managers to run projects successfully. He offers a qualitative case study explaining the importance of Commitment, Communication, Knowledge, Motivation, Role Model, and Teamwork.